Administration of protopine prevents mitophagy and acute lung injury in sepsis - Xiao, Zhong; Long, Juan; Zhang, Jie; Qiu, Zhimin; Zhang, Chen; Liu, Hongbing; Liu, Xinyong; Wang, Kang; Tang, Yahui; Chen, Longwang; Lu, Zhongqiu; Zhao, Guangju (Frontiers in Pharmacology, 2023)
Introduction: Sepsis is a severe life-threatening infection that induces a series of dysregulated physiologic responses and results in organ dysfunction. Acute lung injury (ALI), the primary cause of respiratory failure brought on by sepsis, does not have a specific therapy. Protopine (PTP) is an alkaloid with antiinflammatory and antioxidant properties. However, the function of PTP in septic ALI has not yet been documented. This work sought to investigate how PTP affected septic ALI and the mechanisms involved in septic lung damage, including inflammation, oxidative stress, apoptosis, and mitophagy. Methods: Here, we established a mouse model induced by cecal ligation and puncture (CLP) and a BEAS-2B cell model exposed to lipopolysaccharide (LPS). Results: PTP treatment significantly reduced mortality in CLP mice. PTP mitigated lung damage and reduced apoptosis. Western blot analysis showed that PTP dramatically reduced the expression of the apoptosis-associated protein (Cleaved Caspase-3, Cyto C) and increased Bcl-2/Bax. In addition, PTP decreased the production of inflammatory cytokines (IL-6, IL-1β, TNF-α), increased glutathione (GSH) levels and superoxide dismutase (SOD) activity, and decreased malondialdehyde (MDA) levels. Meanwhile, PTP significantly reduced the expression of mitophagy-related proteins (PINK1, Parkin, LC-II), and downregulated mitophagy by transmission electron microscopy. Additionally, the cells were consistent with animal experiments. Discussion: PTP intervention reduced inflammatory responses, oxidative stress, and apoptosis, restored mitochondrial membrane potential, and downregulated mitophagy. The research shows that PTP prevents excessivemitophagy and ALI in sepsis, suggesting that PTP has a potential role in the therapy of sepsis.